Production of acoustic waves from pulsed thermal radiation. (18th December 2015) - Chen, Kuan; Rahman, Aowabin; Kim, Yeongmin; Oh, Seung Jin; Chun, Wongee
Summary: Generation of acoustic waves from a pulsed thermal radiation beam was experimentally investigated in this paper. Unlike other TACs (thermal acoustic converters), acoustic wave frequencies and phases of this type of TACs can be easily adjusted and controlled—a feature essential to the synchronization of TACs in an array. The TACs we developed were made up of a cylindrical aluminum housing, a glass cover, and metallic wool for effective thermal‐to‐acoustic energy conversion. Radiation emitted from an infrared heater was chopped at a constant frequency prior to entering the converter through the glass cover. The metallic wool was periodically heated by the pulsed radiation beam and cooled because of heat losses to the surroundings. Experiments were conducted for different converter designs and metallic wools, as well as different chopper speeds and radiation intensities. The amplitudes of generated sound waves were found to be dependent on the radiation intensity, the grade and properties of the metallic wool, and the cooling rate of the wool. Higher radiation intensities and thinner wools of lower thermal conductivity produced sounds of higher amplitude. More effective cooling of the metallic wool also helped. Acoustic energy output can also be enhanced by reducing the amount of air in the converter. Copyright © 2015 John Wiley & Sons, Ltd. Abstract : Generation of acoustic waves from a pulsed thermal radiation beam was experimentally investigated. The thermal acoustic converters were made up of a cylindrical aluminum housing, a glass cover, and metallic wool for effective thermal‐to‐acoustic energy conversion. Higher radiation intensities and thinner wools of lower thermal conductivity produced sounds of higher amplitude. More effective cooling of the metallic wool and less air in the converter also helped. Cooling of the metallic wool could be enhanced by increasing the length of the wool before it reached its optimal length.